Accounting for external users: an analysis of Brazilian scientific production in light of the ANPCONT congress from 2007 to 2016 - Ribeiro, Henrique César Melo (Contextus - Revista Contemporânea de Economia e Gestão, 2017)
This study aimed to investigate the profile of the works presented at the National Association of Accountancy Graduate Programs (ANPCONT) congresses from 2007 to 2016 that were related to accounting for external users. Methodologically, the research used the techniques of bibliometric and sociometric analyses. Among the main findings, Fernando Dal-Ri Murcia, Marcelo Alvaro da Silva Macedo and Roberto Carlos Klann turned out to be the most prolific authors. The most productive institutions were: USP, Fucape, UFPB, FURB, UFC and UFRJ. Low density and, at the same time, a high level of degree centrality and of intermediation centrality were observed in co-authorship networks and institutions. The most published topics were: result-oriented management, international accounting standards, disclosure, corporate governance, accounting information, investment, auditing, voluntary disclosure, public management and environmental disclosure.